The prevalence of the clinical preventive health care services of the University Health Centre, IIUM - Tin, Myo Han; Abdullah, Fa’iza; Abdullah, Noraini (2012)
University Health Centre, International Islamic University, (UHC-IIUM), Kuantan campus started using the electronic medical record (EMR) in 2008 for all patients’ data in order to provide quality primary care services to students, staff and their dependents. Even though medical services is routinely given to the community, clinical preventive services (CPS) which include counseling, screening, immunization & chemoprophylaxis which are cost effective should be emphasized to promote health status of the community. One study title Lifestyle Practices And Prevalence Of Obesity In A Community Within A University Campus 2005 (Department of Social and Preventive Medicine, Faculty of Medicine, University of Malaya) reveals that the community did have some unhealthy lifestyle practices such as smoking (27.7%; 95%CI 20.2%, 36.2%), low prevalence of adequate exercise (13.8%;95%CI 8.4%, 21.0%); high prevalence of overweight and obesity (64%; 95%CI 55.1%,72.3%); and high prevalence of co-morbidities such as diabetes mellitus and cardiovascular diseases. These high risk factors of CVD and high prevalence of co-morbidities can be reduced by appropriate CPS. Thus, clinical Preventive Services (CPS) currently provided by UHC is analyzed to get baseline data to propose effective & appropriate CPS for the future plan to improve the existing services.